Experiences of LGBTphobia in Higher Education: A Systematic Review - Silva, Angélica Maria de Sousa; Bessa, Letícia Leite; Girão, Vítor Parente e; Maia, Luciana Maria (Psicologia e Saber Social, 2022)
This investigation aims to characterize and discuss studies that deal with the experiences of LGBTphobia in higher education from the perspective of LGBTQIAPN+ university students. A systematic review was carried out using five databases (PsycArticles, PsycInfo, LILACS, SciELO and PePSIC), in Portuguese, Spanish and English, based on 148 combinations of descriptors related to the topic. The search, carried out in November 2022, retrieved 1,272 complete empirical articles. After two filterings, 17 articles remained, published between 2017 and 2022. Most of the articles are from research carried out in the United States and have a qualitative design. The analysis extracted four thematic categories: 1) Violence suffered by LGBTQIAPN+ university students on campus; 2) Impacts of LGBTphobia on the lives of LGBTQIAPN+ university students; 3) LGBTphobia and intersections; and 4) Individual and institutional strategies for combating LGBTphobia. It is concluded that LGBTphobia is a reality present in the university environment that impacts the experiences and permanence of LGBTQIAPN+ students. However, there are many possibilities for coping that can and should be promoted by higher education institutions, to build academic environments that are safer, more inclusive and favorable to the well-being of LGBTQIAPN+ people. This study suggests that there is a complexity of experiences faced by students belonging to sexual and gender minorities in higher education, related to violence, discrimination, intersections between different forms of prejudice, and impacts on mental health. Institutional measures can be implemented to address LGBTphobia and build safer, more inclusive, and conducive academic environments for the well-being of all.